UPAYA MENINGKATKAN HASIL BELAJAR IPA DANBAHASA INDONESIA SISWA KELAS V A MELALUI MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING)SD NEGERI 007 BAGAN BESAR - Raihan ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe the learning outcomes through the use of media map. The subjects were students of class 007 VA SD Negeri Besar Bagan Bagan great learning results. This research is a class action, the research was conducted by two cycles. Collecting data in this study using observation techniques and activities of teacher and student achievement test. This research is to apply the learning model CTL. The results showed that the learning outcomes and Indonesian IPA increases it is characterized by increased mastery (mastery) students to the learning material of 60% and above, in the second cycle are as many as 22 out of 25 students or 85% for science subjects. In subjects Indonesian 23 students from 25 students or 92%. Student mastery of the learning material is less than 60% as much as three students from 25 students or 15% in science subjects. In subjects Indonesian 2 students from 25 students or 8%. Based on this it can be concluded that the application of the model CTL can improve science learning outcomes and Indonesian.